Sodium-ion battery positive electrode material as well as preparation method and application thereof
By doping element A into the positive electrode material of sodium ion battery and forming a zinc zirconium phosphate coating, the problem of irreversible changes in the structure and low energy density of sodium ion battery under high voltage conditions is solved, and the cycle stability and life of the battery are improved , achieving more efficient energy storage and use.
Patent Information
- Application Number
- CN202411300245.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-17
AI Technical Summary
Sodium ion batteries have problems such as irreversible changes in the structure of the positive electrode material and low energy density under high voltage conditions, which affects their performance and life.
By doping A elements (such as Ca, Sr, Ba, Mg) into the positive electrode material of sodium ion battery and forming a zinc zirconium phosphate coating, the structural stability of the material at high voltage is enhanced, and the transition metal ion migration and oxygen precipitation are prevented. , improve cycle stability and service life.
It effectively improves the performance of sodium ion batteries at high voltages, extends the operating life of the batteries, and improves its reliability and economicality in practical applications.
Smart Images

Figure CN119153655A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries and relates to a sodium ion battery positive electrode material and a preparation method and application thereof. Background Art
[0002] With the acceleration of industrialization and the growing demand for energy, the status of fossil fuels such as oil and coal as the main energy source has begun to be challenged. These traditional energy sources are not only limited in reserves, but also the environmental pollution problems caused by their mining and use are increasingly attracting people's attention. In order to meet this challenge, finding alternative traditional energy sources has become a key direction of global research. In this context, clean energy has gradually emerged and become an important part of sustainable development. Among them, the development of lithium battery technology is particularly eye-catching. From the early lithium metal batteries to the widely used lithium-ion batteries today, lithium batteries have dominated the fields of portable electronic devices, electric vehicles, and energy storage systems with their high energy density and long service life.
[0003] However, the price of lithium cobalt oxide, a key raw material for lithium-ion batteries, has risen sharply in recent years, which has not only pushed up the manufacturing cost of lithium-ion batteries, but also caused instability in the supply chain. At the same time, sodium-ion batteries have gradually entered the public eye as a potential alternative due to the abundant reserves of sodium in the earth's crust and its excellent low-temperature performance and safety. Sodium-ion batteries have a similar working mechanism to lithium-ion batteries, both of which realize the charging and discharging process through the movement of ions between the positive and negative electrodes.
[0004] Nevertheless, sodium-ion batteries have some inherent technical challenges compared to lithium-ion batteries. First, the charge cutoff voltage of sodium-ion batteries is much lower than that of lithium-ion batteries. This is because, under high voltage conditions, metal ions in transition metal oxides may migrate to the negative electrode, and oxygen ions may precipitate as oxygen. This chemical change will cause irreversible changes in the structure of the positive electrode material, thereby reducing the overall performance and service life of the battery. Secondly, the lower charge cutoff voltage also means that the charge and discharge capacity of sodium-ion batteries is smaller, that is, it can store and release less energy than lithium-ion batteries. Therefore, although sodium-ion batteries have obvious advantages in resource abundance and safety, they still need to overcome problems such as low energy density in practical applications.
[0005] A Chinese patent application document (CN117497728A) discloses a positive electrode material for a sodium ion battery, in which the nano-coating material contains calcium carbonate or calcium oxide. Calcium carbonate will react with the acid in the electrolyte and consume the electrolyte; while calcium oxide is sensitive to moisture and easily reacts with moisture in the air to form calcium hydroxide and generate a large amount of heat. These reactions will destroy the coating layer and affect performance.
[0006] The Chinese patent application document (CN117117174A) discloses a sodium ion battery positive electrode material and its preparation method and application. Among the coating materials mentioned, WO 3 It can react with the residual alkali on the surface of the positive electrode material and the hydrofluoric acid in the electrolyte; SrO easily absorbs moisture and carbon dioxide in the air, and can react to generate strontium hydroxide when absorbing water, but these will destroy the coating layer and affect the material performance. Summary of the invention
[0007] The purpose of the present invention is to address the above-mentioned problems existing in the prior art and to propose a positive electrode material for a sodium ion battery, so as to improve the performance of the battery at high voltage, increase the capacity, and ultimately extend the working life of the battery.
[0008] The purpose of the present invention can be achieved by the following technical solutions:
[0009] A sodium ion battery positive electrode material, the chemical formula of the sodium ion battery positive electrode material is Na a Ni b Fe c Mn d O 2 A e B,
[0010] Among them, 0.88≤a≤1, a+e×2=1, 0.2≤b≤0.4, 0.2≤c≤0.4, 0.2≤d≤0.4, b+c+d=1, 0.001≤e≤0.06;
[0011] Among them, element A is at least one of Ca, Sr, Ba, and Mg, and element B is zinc zirconium phosphate.
[0012] The present invention improves the stability of the positive electrode material of the sodium ion battery under high voltage conditions by doping a small amount of element A and coating with B. This method can effectively improve the electrochemical properties of the material without significantly changing the basic structure and physical and chemical properties of the material. Specifically, the addition of A and B can enhance the structural stability of the positive electrode material under high voltage conditions, prevent the migration of transition metal ions to the negative electrode and the precipitation of oxygen, thereby avoiding irreversible structural changes in the positive electrode material caused by high voltage, and thus improve the cycle stability and service life of the battery. In this way, the present invention not only improves the performance of the sodium ion battery under high voltage, but also maintains the structural integrity of the material itself, ensuring the high-efficiency operation of the battery throughout its life cycle. In addition, the design of the material also takes into account the needs of practical applications. By precisely controlling the amount of doping, the material further improves its reliability and economy in practical application scenarios while maintaining its original advantages.
[0013] In the above-mentioned sodium ion battery positive electrode material, B is a coating layer, and the coating layer thickness is 20-70nm. The present invention needs to control the coating layer thickness to 20-70nm. If the coating layer is too thin, it is impossible to effectively isolate the direct contact between the positive electrode material body and the electrolyte. In this case, the positive electrode material may react with the electrolyte during the charge and discharge process, resulting in damage to the material structure, thereby affecting the cycle stability and service life of the battery. On the contrary, if the coating layer is too thick, the ohmic polarization of the material will increase, thereby affecting the charge transfer efficiency at the interface. This means that during the charge and discharge process, electrons and ions need to pass through a thicker coating layer to complete the transfer, which increases the resistance to charge transfer and reduces the overall energy efficiency of the battery. In addition, an overly thick coating layer may also cause the weight of the material to increase, thereby affecting the energy density of the battery.
[0014] The present invention also provides a method for preparing the above-mentioned sodium ion battery positive electrode material, the method comprising the following steps:
[0015] S1, uniformly mixing the sodium source, the A source and the nickel-iron-manganese precursor, sintering them at a heat preservation temperature, and crushing them after natural cooling to obtain a sintered product;
[0016] S2, mixing phosphate, zinc source and zirconium source evenly and soaking them with ethanol, and then ball milling and heat-drying to obtain B;
[0017] S3, sintering the sintered product and B at a heat preservation condition to obtain a positive electrode material for a sodium ion battery.
[0018] Preferably, the sodium source includes at least one of sodium carbonate and sodium oxalate.
[0019] Preferably, the phosphate is diammonium phosphate.
[0020] Zinc sources include hydroxides and salts containing the element zinc.
[0021] More preferably, the zinc source is zinc hydroxide.
[0022] Zirconium sources include hydroxides and salts containing the element zirconium.
[0023] More preferably, the zirconium source is zirconium hydroxide.
[0024] In the above-mentioned method for preparing a positive electrode material for a sodium ion battery, the sintering temperature in step S1 is 900-990°C and the time is 14-17h. The present invention needs to control the sintering temperature to 900-990°C and the time to 14-17h. The temperature within this range can ensure the full sintering of the material without generating impurities, while avoiding the deterioration of the material performance caused by excessively high temperature. Reasonable sintering temperature and time not only help to obtain pure positive electrode materials, but also ensure that the material has a good microstructure, which is conducive to improving the comprehensive performance of the battery.
[0025] If the sintering temperature is too low, for example, below 900 degrees Celsius, impurities may be generated during the sintering process. The presence of impurities will affect the purity of the material, which in turn will lead to a decrease in the electrochemical performance of the battery. For example, impurities may reduce the conductivity of the material and affect the insertion and deinsertion process of lithium / sodium ions, thereby reducing the capacity and cycle stability of the battery.
[0026] If the sintering temperature is set too high, exceeding 990 degrees Celsius, although no obvious impurities may be produced, the performance of the material will be affected. High-temperature sintering may cause excessive growth and agglomeration of material particles, which will not only increase the contact resistance between particles and reduce the conductivity of the material, but also reduce the specific surface area of the material, affecting the diffusion rate of ions, and ultimately leading to a decrease in the cycle performance of the battery. In addition, high temperature may also change the crystal structure of the material, further affecting its electrochemical behavior.
[0027] In the above-mentioned method for preparing a positive electrode material for a sodium ion battery, the ball milling speed in step S2 is 350-450 rpm, and the ball milling time is 3-5 h.
[0028] In the above-mentioned method for preparing a positive electrode material for a sodium ion battery, the heat preservation and drying temperature is 80-85° C. and the time is 4-6 hours.
[0029] In the above-mentioned method for preparing a positive electrode material for a sodium ion battery, the sintering temperature in step S3 is 600-850° C. and the time is 12-14 hours.
[0030] The present invention also provides a sodium ion battery positive electrode sheet, which comprises the positive electrode material.
[0031] The present invention also provides a sodium ion battery, which comprises the above-mentioned positive electrode material.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The present invention ensures the stability of the internal structure of the material and the maximization of the electrochemical activity by precisely controlling the chemical ratio of the positive electrode material. The strict definition of the chemical formula helps to ensure that the material maintains good structural integrity in different voltage ranges, avoiding the occurrence of transition metal ion migration and oxygen precipitation, thereby reducing the irreversible structural changes of the positive electrode material caused by high voltage;
[0034] 2. The present invention further enhances the stability of the material by forming a coating layer composed of zirconium zinc phosphate on the surface of the positive electrode material. This coating layer can not only effectively prevent the electrolyte from directly contacting the active material and reduce the occurrence of side reactions, but also alleviate the volume change of the material during the cycle to a certain extent, thereby improving the cycle stability and overall life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The 25°C cycle test curves of sodium ion batteries prepared with positive electrode materials of Example 1 and Comparative Example 1, respectively, have a charging current of 0.5C, a discharging current of 1C, and a voltage range of 1.5V-4.1V. DETAILED DESCRIPTION
[0036] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.
[0037] Embodiment 1:
[0038] S1. Prepare raw materials according to the molar ratio of Na:Sr:Ni:Fe:Mn of 0.88:0.06:0.33:0.33:0.33:0.33:
[0039] The sodium source is sodium carbonate;
[0040] S2, uniformly mixing the sodium source, the A source, and the nickel-iron-manganese precursor, sintering at 935° C. for 15 h, and crushing after natural cooling to obtain a sintered product;
[0041] S3, mixing phosphate, zinc source and zirconium source evenly and soaking them with ethanol, ball milling at 390 rpm for 4 h, and then drying at 82 ° C for 5 h to obtain zirconium zinc phosphate;
[0042] The phosphate is ammonium dihydrogen phosphate, the zinc source is zinc hydroxide, and the zirconium source is zirconium hydroxide.
[0043] S4. The sintered product and zinc zirconium phosphate are sintered at 800° C. for 13 h to obtain a sodium ion battery positive electrode material with a coating layer thickness of 50 nm.
[0044] Embodiment 2:
[0045] S1. Prepare raw materials according to the molar ratio of Na:Ba:Ni:Fe:Mn of 0.88:0.06:0.33:0.33:0.33:0.33: sodium source, Sr, nickel iron manganese precursor;
[0046] The sodium source is sodium carbonate;
[0047] S2, uniformly mixing the sodium source, the A source, and the nickel-iron-manganese precursor, sintering at 935° C. for 15 h, and crushing after natural cooling to obtain a sintered product;
[0048] S3, mixing phosphate, zinc source and zirconium source evenly and soaking them with ethanol, ball milling at 390 rpm for 4 h, and then drying at 82 ° C for 5 h to obtain zirconium zinc phosphate;
[0049] The phosphate is ammonium dihydrogen phosphate, the zinc source is zinc hydroxide, and the zirconium source is zirconium hydroxide;
[0050] S4. The sintered product and zinc zirconium phosphate are sintered at 800° C. for 13 h to obtain a positive electrode material for a sodium ion battery.
[0051] Embodiment 3:
[0052] S1. Prepare raw materials according to the molar ratio of Na:Mg:Ni:Fe:Mn of 0.88:0.06:0.33:0.33:0.33:0.33: sodium source, Sr, nickel iron manganese precursor;
[0053] The sodium source is sodium carbonate;
[0054] S2, uniformly mixing the sodium source, the A source, and the nickel-iron-manganese precursor, sintering at 935° C. for 15 h, and crushing after natural cooling to obtain a sintered product;
[0055] S3, mixing phosphate, zinc source and zirconium source evenly and soaking them with ethanol, ball milling at 390 rpm for 4 h, and then drying at 82 ° C for 5 h to obtain zirconium zinc phosphate;
[0056] The phosphate is ammonium dihydrogen phosphate, the zinc source is zinc hydroxide, and the zirconium source is zirconium hydroxide;
[0057] S4. The sintered product and zinc zirconium phosphate are sintered at 800° C. for 13 h to obtain a positive electrode material for a sodium ion battery.
[0058] Embodiment 4:
[0059] The only difference from Example 1 is that the coating layer thickness is 10 nm.
[0060] Embodiment 5:
[0061] The only difference from Example 1 is that the sintering temperature in step S4 is 500°C.
[0062] Embodiment 6:
[0063] The only difference from Example 1 is that the sintering temperature in step S4 is 1000°C.
[0064] Comparative Example 1:
[0065] The only difference from Example 1 is that the molar ratio of Na:Sr:Ni:Fe:Mn is 0.998:0.001:0.33:0.33:0.33.
[0066] Comparative Example 2:
[0067] The only difference from Example 1 is that the molar ratio of Na:Sr:Ni:Fe:Mn is 0.8:0.10:0.33:0.33:0.33.
[0068] Comparative Example 3:
[0069] The only difference from Example 1 is that the molar ratio of Na:Sr:Ni:Fe:Mn is 0.98:0.01:0.33:0.33:0.33.
[0070] Comparative Example 4:
[0071] The only difference from Example 1 is that Sr is not added to the raw materials.
[0072] Comparative Example 5:
[0073] The only difference from Example 1 is that in step S4, the sintered product is directly sintered at 800° C. for 13 hours.
[0074] A sodium ion soft pack battery is prepared according to the following steps:
[0075] 1. Preparation of positive electrode sheet: Under a certain temperature and humidity environment, the positive electrode material prepared in Example 1-6 and Comparative Example 1-5 is homogenized in a ratio of super-P: PVDF = 96:2:2, and the material is discharged, coated, rolled, and punched to obtain a positive electrode sheet when the viscosity and fineness meet the requirements.
[0076] 2. Negative electrode sheet production: homogenize according to the ratio of hard carbon: super-P: CMC: SBR = 95:1:2:2, discharge the material under the required viscosity and fineness, coat, roll and punch to obtain the negative electrode sheet, the CB value is 1.25. 3. Diaphragm: ceramic diaphragm. 4. Battery cell stacking: stack the positive electrode sheet, diaphragm and negative electrode sheet into bare battery cells, encapsulate them with aluminum plastic film, bake them in an oven at 85°C for 2 days, test the moisture content of the battery cells, and after the moisture content passes the test, perform liquid injection, first sealing, formation, volume separation and second sealing.
[0077] The assembled sodium-ion battery was subjected to room temperature cycle test in the voltage range of 1.5-4.1V.
[0078] Figure 1The 1.5-4.1V room temperature cycle curves of Example 1 and Comparative Example 1 are shown. The test temperature is 25±2°C, and the test conditions are 0.5C constant current charging and 1C constant current discharging. After 100 cycles, the capacity retention rate of Example 1 is 99.89%, while the capacity retention rate of Comparative Example 1 is 92.43%. Within a suitable range, the more calcium content, the more conducive it is to stabilizing the structure of the positive electrode material, thereby obtaining a better capacity retention rate during room temperature cycling.
[0079] Table 1: Performance test results of positive electrode materials prepared in Examples 1-6 and Comparative Examples 1-5 after being used in sodium ion soft pack batteries
[0080]
[0081]
[0082] The parts of the embodiments herein that are not exhaustive of the midpoint values of the technical scope claimed for protection by the present invention and the new technical solutions formed by equivalent replacement of single or multiple technical features in the technical solutions of the embodiments are also within the scope claimed for protection by the present invention; at the same time, in all the listed or unlisted embodiments of the scheme of the present invention, each parameter in the same embodiment merely represents an example of its technical solution (i.e., a feasible solution), and there is no strict coordination and limitation relationship between the parameters, wherein the parameters can be replaced with each other without violating the axioms and the claims of the present invention, unless otherwise stated.
[0083] The technical means disclosed in the scheme of the present invention are not limited to the technical means disclosed in the above technical means, but also include technical schemes composed of any combination of the above technical features. The above is a specific implementation of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also regarded as the protection scope of the present invention.
[0084] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. A sodium ion battery positive electrode material, characterized in that: The chemical formula of the sodium ion battery positive electrode material is Na a Ni b Fe c Mn d O2A e B, Among them, 0.88≤a≤1, a+e×2=1, 0.2≤b≤0.4, 0.2≤c≤0.4, 0.2≤d≤0.4, b+c+d=1, 0.001≤e≤0.06; Among them, element A is at least one of Ca, Sr, Ba, and Mg, and element B is zinc zirconium phosphate.
2. A sodium ion battery positive electrode material according to claim 1, characterized in that: B is a coating layer, and the coating layer thickness is 20-70nm.
3. A method for preparing a positive electrode material for a sodium ion battery as claimed in claim 1, characterized in that: The method comprises the following steps: S1, uniformly mixing the Na source, A source and nickel-iron-manganese precursor, sintering at a heat preservation temperature, and crushing after natural cooling to obtain a sintered product; S2, mixing phosphate, zinc source and zirconium source evenly and soaking them with ethanol, and then ball milling and heat-drying to obtain B; S3, sintering the sintered product and B at a heat preservation condition to obtain a positive electrode material for a sodium ion battery.
4. The method for preparing a positive electrode material for a sodium ion battery according to claim 3, characterized in that: The sintering temperature in step S1 is 900-990°C and the sintering time is 14-17h.
5. The method for preparing a sodium ion battery positive electrode material according to claim 3, characterized in that: In step S2, the ball milling speed is 350-450 rpm, and the ball milling time is 3-5 h.
6. The method for preparing a positive electrode material for a sodium ion battery according to claim 3, characterized in that: The heat preservation and drying temperature is 80-85℃ and the time is 4-6h.
7. The method for preparing a positive electrode material for a sodium ion battery according to claim 3, characterized in that: In step S3, the sintering temperature is 600-850°C and the sintering time is 12-14 hours.
8. A sodium ion battery positive electrode sheet, characterized in that: The sodium ion battery positive electrode sheet comprises the positive electrode material according to any one of claims 1 to 7.
9. A sodium ion battery, characterized in that: The sodium ion battery comprises the positive electrode material according to any one of claims 1 to 7.
Citation Information
Patent Citations
Sodium-ion battery positive electrode material as well as preparation method and application thereof
CN117117174A
Sodium-ion battery positive electrode material and preparation method thereof
CN117497728A
